THE INFLUENCE OF TRUST AND COMMITMENT AT BANK BRI KCP UNIT MOTOLING - Pelle, Nathasya F.; Tulung, Joy E.; Saerang, Regina T. (Universitas Sam Ratulangi, 2021)
The purpose of this research is to find out the influence of Trust and Commitment in the Banking Industry, and a lot of the banking industry is looking for ways to achieve its goal. There are many strategies to build relationships with customers, one of them this study to know the influence of trust and commitment at BRI KCP Unit Motoling. How BRI implemented trust and commitment to their customer. The objective of this study to find out about the trust and commitment influence the customer at BRI KCP Unit Motoling. Theories that are used in this research are theories about trust and commitment. The population of this research is all customers BRI KCP Unit Motoling. And the sample is 10 respondents of customers BRI KCP Unit Motoling, these 10 respondents take from the different of occupation. This research used qualitative analysis methods and also using interview and observation techniques. The result and conclusions of this study indicate the application of trust and commitment to customer at BRI KCP Unit Motoling have a positive statement from 10 informants and bonding based on the trust and commitment. This is caused good and best services towards the customer of the bank itself. There are two recommendations in this research: first, trust and commitment are the activities that the bank must consider in order to build a positive and long-term relationship with customers, create more profit that gifts more benefit not only to the company but also give more benefit to customers. Second, the bank must give more improve how to deliver quick information to provide the right information to the customer.Keywords: trust, commitment, consumer behavior